ATTITUDE OF TEACHERS TOWARDS DELAYED STUDENTS IN MAINSTREAM CLASSROOMS AT ELEMENTARY LEVEL IN PAKISTAN - Nadia Mehrukh; Wajid Mahnaz; Hina Iqbal; Dr. Iffat Basit (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
After becoming signatory of UNCRPD, inclusive education is a reality for approaching days, however, due to our already weak and socio-religiously confused educational system, teacher as well as parents of delayed students are not ready to accept them in mainstream classrooms. The basic reason of such reluctance is lack of awareness as well as fears of added responsibilities, which may be associated with this major shift in educational methodology. The major component of inclusive education concept revolves around the attitude and perception of teachers, which needs detailed elaboration. In this study, mixed method research (both qualitative and quantitative) was used. The research instrument was developed according to the directions and guidance provided by experts with fourteen items, which was then shared with 100 elementary school teachers belonging from different Federally administered educational institutions in District Okara and their responses were quantified for analysis. Moreover, to obtain clear perspective of the issue, interview of senior teachers from same educational institutions were conducted too. Basing on acquired data, results were finalized which showed reluctance by teachers due to lack of awareness as well as fear of additional responsibilities and expectations without any visible incentive. Moreover, neither required human resources nor infrastructures allow immediate adoption of inclusive schooling system. Thus, gradual approach towards implementation of new concept along with concrete steps by government is found the most viable option for approaching the issue.